DASHBOARD PENJUALAN BARANG BERBASIS WEB DI TOKO BMB COSMETIC SEMARANG - ABDUR RAFI, IRFAN; Alfa Razaq, Jeffri (Information Technology and Telematics, 2018)
ABSTRAK BMB COSMETIC Shop is a business that is engaged in cosmetic sales. The system in the cosmetic sales shop only uses simple bookkeeping. Here it is said to be simple because the sales or purchase transaction process is still using a manual recording system and in the store sales there is a target of a sale that is still packaged simply. Data collection methods used are methods of observation, interviews and literature study. The system development methodology in this study uses the Prototype methodology. The results in this study are the creation of a web-based item sales dashboard application in Semarang Cosmetic BMB store.